National Trends in Heart Failure and Acute Myocarditis–Related Death Before and During the COVID‐19 Pandemic - Rabbia Siddiqi; Syed H. Farhan; Syeda A. Shah; Hasan Mushahid; Muhammad M. Nasir; George V. Moukarbel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The COVID‐19 pandemic saw a rise in cardiovascular death, likely the result of disruptions in health care delivery and the infection itself. We examine mortality trends of heart failure (HF) and acute myocarditis (AM) before and during the pandemic and identify the most affected demographic subgroups. Methods and Results We queried the Centers for Disease Control and Prevention Wide‐Ranging Online Data for Epidemiologic Research database for deaths from HF and AM before (1999–2019) and during (2020–2021) the COVID‐19 pandemic. Age‐adjusted mortality rates were calculated and stratified by sex, race and ethnicity, and age category. Trend‐level analysis was performed using the Joinpoint Regression Program, which estimates average annual percentage change (AAPC) in age‐adjusted mortality rate with corresponding 95% CI. A total of 7 366 944 HF deaths and 33 750 AM deaths occurred during 1999 to 2021. HF and AM mortality rates downtrended before the pandemic (AAPC, −0.63 and −2.42, respectively) but reversed during the pandemic (HF AAPC, 7.91; and AM AAPC, 20.3). Overall, during the pandemic, the age‐adjusted mortality rate for both HF and AM was greater for men, non‐Hispanic Black people, and adults aged ≥65 years. The sharpest increase was observed among non‐Hispanic American Indian people (AAPC, 14.9), Hispanic people (AAPC, 9.63), and young adults (AAPC, 20.9) for HF and among women (AAPC 18.7), non‐Hispanic Black people (AAPC, 15.6), and older adults (AAPC, 23.5) for AM. Conclusions The prepandemic downward trends of HF and AM mortality rates have reversed since 2020. Subgroups that had the greatest absolute mortality rates from both AM and HF in the pandemic years were men, non‐Hispanic Black people, and older adults (aged ≥65 years).